Agricultural Development and Climate Change Adaptation Planning Tool (ADAPT) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We have developed this tool for India and pilot test has been done for the state Uttar Pradesh. District level crop production, cost of input use, land use, commodity price and demand are among the key input data we have used to solve this model.